PENGARUH MEDIA KONKRET TERHADAP PEMAHAMAN SISWA PADA MATERI WUJUD BENDA KELAS IV UPTD SDN BURNEH 1 BANGKALAN - Rahayu, Nur Fitriyanti; Pratiwi, Siska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Class IV teachers in teaching science learning on material material only use lecture methods and learning resources, making learning very observant and boring and the average value of science learning is still below the Minimum Completeness Criteria, namely 52.8. This research aims to determine the effect of concrete media on students' understanding of material in class IV UPTD SDN Burneh 1 Bangkalan. This research uses quantitative research using experimental methods and research design using one group pretest-posttest. The data collection method used in this research was a test. The data analysis methods used in this research are Validity Test, Reliability Test, Normality Test and Paired Sample T-Test Hypothesis Test. Based on the research results, the sig. The paired sample t-test of 0.000 < 0.05 shows that there is an influence of concrete media on students' understanding of material in class IV UPTD SDN Burneh 1 Bangkalan.